In the court we trust : cooperation, coordination and collaboration between the ECJ and supreme administrative courts / Rob van Gestel, Jurgen de Poorter. - Gestel, Rob van; Poorter, J. C. A. de (Jurgen C. A.), 1974- (Cambridge studies in european law and policy., 2019)
The preliminary reference procedure has long been envisaged as a judicial dialogue between the European Court of Justice and national courts. However, in reality the relationship appears to be closer to one of growing separation rather than to a happy marriage between equal partners. This book tries to find out: what is behind this? A study of the existing literature, combined with a case law analysis and interviews with judges, has shown that there are a number of important stumble blocks hindering the communication between these courts, such as language barriers, time constraints, and a failing digital infrastructure. However, on a deeper level there also appears to be a lack of mutual trust that prevents Supreme Administrative Courts from using the possibilities the procedure provides, such as the opportunity to offer provisional answers to the Court of Justice and the use of requests for clarification by the latter.